Factors influencing social demands of aquatic ecosystems - Joseph E. Flotemersch; Samantha M. Shattuck; Kelsey B. Aho; Clayton E. Cox; Maryann R. Cairns (Ecology and Society, 2019)
Aquatic ecosystems provide services essential to human health and economies. Therefore, resource management programs aim to ensure the sustainable flow of these services. Stakeholder engagement is often a critical tool in learning what services are of priority to the public and may be integral to the success of aquatic ecosystem management because public participation in planning and decision making can generate broader support, e.g., financial, intellectual, and labor, for the management plan. The collection of such information may even be statutorily mandated, such as in the Clean Water Act of the United States, which requires that water bodies be classified for the beneficial uses, e.g., fisheries, drinking water, or recreation, they provide. Past evaluations of stakeholder engagement with aquatic ecosystems have considered a wide range of factors influencing engagement. We conducted a critical review of the literature on characteristics of stakeholders and characteristics of the environment that influence stakeholder engagement and participation with aquatic ecosystems. Our objective was to identify factors that should be considered in the creation of surveys to help encourage the inclusion of ecological and social beneficial uses data in large-scale water monitoring programs. Factors identified in our review were, extent and influence of place-based knowledge; proximity to, and frequency of visitation of the resource(s) being considered; basic demographics such as age, gender, education, and income; home community type; aesthetic appeal of the resource; and primary reason for engagement with the resource. We propose these factors, with subfactors, as a template for survey development.